PROFILING PESERTA DIDIK DI ERA DIGITAL: PELUANG DAN TANTANGAN BAGI GURU SEKOLAH DASAR - Risma Herdianti; Rosmayanti; Putri Pikrin, Salsabila; Ilah Nurlaelah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has significantly transformed the learning characteristics of elementary school students, requiring teachers to develop a comprehensive understanding of individual learner profiles. Student profiling has emerged as a strategic approach to identifying students’ cognitive, socio-emotional, and digital characteristics as a foundation for designing adaptive learning. This article aims to systematically examine the concept of student profiling in the digital era, identify opportunities for elementary school teachers, and analyze the challenges of its implementation. The study employed a Systematic Literature Review (SLR) method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Literature searches were conducted through Google Scholar, Scopus, ERIC, DOAJ, and SINTA databases, covering articles published between 2021 and 2026. Out of 487 identified articles, 35 met the inclusion criteria and were analyzed in depth. The findings indicate that digital-based student profiling has significant potential to support personalized learning, early identification of learning difficulties, and the development of data-driven adaptive learning strategies. However, its implementation continues to face challenges, including limited teachers’ digital literacy, data privacy and security concerns, technological infrastructure disparities, and increasing administrative burdens. This study concludes that successful implementation of student profiling requires continuous enhancement of teachers’ professional competencies, clear data protection policies, and adequate institutional support to promote effective and ethical learning practices in elementary schools.